Applications on operations on weakly compact generalized topological spaces - Roy, B.; Noiri, T. (Carpathian Mathematical Publications, 2020)
In this paper, we have introduced the notion of operations on a generalized topological space (X,μ) to investigate the notion of γ__μ-compact subsets of a generalized topological space and to study some of its properties. It is also shown that, under some conditions, γ__μ-compactness of a space is equivalent to some other weak forms of compactness. Characterizations of such sets are given. We have then introduced the concept of γ__μ-T__2 spaces to study some properties of γ__μ-compact spaces. This operation enables us to unify different results due to S. Kasahara.